2022
DOI: 10.3390/ijms231810495
|View full text |Cite
|
Sign up to set email alerts
|

Development and Molecular Cytogenetic Characterization of a Novel Wheat-Rye T6RS.6AL Translocation Line from Secale cereale L. Qinling with Resistance to Stripe Rust and Powdery Mildew

Abstract: In this study, a novel T6RS.6AL translocation line, 117-6, was selected from a cross between common Chuannong25 (CN25) wheat and Qinling rye. The results of nondenaturing fluorescence in situ hybridization (ND-FISH) and PCR showed that 117-6 contained two T6RS.6AL translocation chromosomes. The distal region of the 6RS chromosome in 117-6 was mutant and showed different FISH signal patterns. When inoculated with different stripe rust races and powdery mildew races in seedlings, 117-6 expressed high resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Genome-specific molecular markers are simple and accurate tools for foreign genetic material analysis. For example, Ren et al [ 54 ] confirmed that the 6RS chromosome was introgressed in wheat-rye line 117-6 using SCAR markers, and Zhang et al [ 55 ] found that Thinopyrum intermedium 6StS.6JsL chromosomes existed in line CH51 through SNP array. Similarly, we determined that D88-2a contained P. huashanica homologous Group 6 chromosomes by comprehensively using multi-type molecular markers (SCAR, STS and SNP array).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-specific molecular markers are simple and accurate tools for foreign genetic material analysis. For example, Ren et al [ 54 ] confirmed that the 6RS chromosome was introgressed in wheat-rye line 117-6 using SCAR markers, and Zhang et al [ 55 ] found that Thinopyrum intermedium 6StS.6JsL chromosomes existed in line CH51 through SNP array. Similarly, we determined that D88-2a contained P. huashanica homologous Group 6 chromosomes by comprehensively using multi-type molecular markers (SCAR, STS and SNP array).…”
Section: Discussionmentioning
confidence: 99%
“…Except for 1RS, other rye chromosomes also contain powdery mildew resistance genes and were introduced into wheat in the form of wheat-rye addition lines, substitution lines or translocation lines. Pm7 derived from Rosen rye 2RL was transferred into wheat in the form of T4BS.4BL-2RL translocation (Driscoll et al 1965), Pm56 from Qinling rye 6RS was brought into wheat in the form of T6RS.6AL translocation (Hao et al 2018;Ren et al 2022b), and Pm20 from Proli c rye was introduced into wheat in the form of T6BS.6RL translocation (Friebe et al 1994). Recently, some reports also indicated rye chromosomes carry powdery mildew resistance genes, including 1RS from Aigan, Weining and Baili rye (li et al 2016; Ren et al 2017Ren et al , 2018, 1R from Austrian rye (Yang et al 2016), 2RL from Jingzhou and German White rye (An et (Ren et al 2020).…”
Section: Introductionmentioning
confidence: 99%